2008
DOI: 10.1785/0120070030
|View full text |Cite
|
Sign up to set email alerts
|

Site Amplification and Attenuation via Downhole Array Seismogram Inversion: A Comparative Study of the 2003 Miyagi-Oki Aftershock Sequence

Abstract: Weak-motion geotechnical array recordings at 38 stations of the Japanese strong-motion network KiK-Net from the 2003 M w 7:0 Miyagi-Oki aftershock sequence are used here to quantify the amplification and attenuation effects of nearsurface formations to incident seismic motion. Initially, a seismic waveform optimization algorithm is implemented for the evaluation of high-resolution, low-strain velocity (V s ), attenuation (Q s ), and density (ρ) profiles at the sites of interest. Based on the inversion results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 84 publications
6
43
0
Order By: Relevance
“…Previous studies have found clear evidences of soil nonlinearity after previous large earthquakes in Japan, including the 1995 M w 6.8 Kobe earthquake, 2000 M w 6.8 Western Tottori earthquake, 2003 M w 8.3 Tokachi-Oki earthquake, 2003 M w 7.0 Miyaki-Oki earthquake, and 2004 M w 6.6 Niigata earthquake (e.g., Pavlenko and Irikura 2002;Sawazaki et al, 2006;Rubinstein et al, 2007;Assimaki et al, 2008;Wu et al, 2009aWu et al, , 2010. The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found clear evidences of soil nonlinearity after previous large earthquakes in Japan, including the 1995 M w 6.8 Kobe earthquake, 2000 M w 6.8 Western Tottori earthquake, 2003 M w 8.3 Tokachi-Oki earthquake, 2003 M w 7.0 Miyaki-Oki earthquake, and 2004 M w 6.6 Niigata earthquake (e.g., Pavlenko and Irikura 2002;Sawazaki et al, 2006;Rubinstein et al, 2007;Assimaki et al, 2008;Wu et al, 2009aWu et al, , 2010. The sharp reductions of the peak frequency and peak spectral ratio followed by gradual recovery observed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that the median estimates (shown here for the same scenario) are not significantly affected by the damping scaling, even at high frequency, while the within-event variability is found significantly larger at high frequency (f [ 4-5 Hz) for the larger damping values. An optimal option might be to define for each site the ''best Q S profile'' in a similar way to what was done by Assimaki et al (2008), with however the risk of a significant trade-off between shallow velocity profiles and Q S values at high frequency. Also, it could be possible to consider a frequency-dependent Q S [Q S (f) = Q S0 9 fa].…”
Section: Comparison Of Dhcor and Surfcor Predictionsmentioning
confidence: 99%
“…Indeed, the nonlinearity susceptibility of a site is a function of both the site conditions and the incident ground-motion intensity and frequency content; while the former describes the strength of the material, the latter represents the amplitude of wavelengths of the same order of magnitude as the soft layers of the profile that may potentially be driven to the nonlinear range. Therefore, a description based on the magnitude distance of the station and the site conditions is not adequate to describe the frequency content of the ground motion (Assimaki et al, 2008).…”
Section: Nonlinearity Susceptibility and Modeling As A Function Of Thmentioning
confidence: 99%